ANALISIS PENDAPATAN USAHATANI PADI SAWAH DI DESA WOSU KECAMATAN BUNGKU BARAT KABUPATEN MOROWALI - Kasya, Moh. (AGROTEKBIS, 2017)
This study aims to determine the magnitude of paddy rice farming income. The research location is at Wosu Village, Western of Bungku Sub District it determined in purposive. This research was conducted in in September until November 2015. The determination of respondent was done by using simple random method (Simple Random Sampling), the number of respondents as a sample was 32 people from the population of 120 families of farmers of paddy. The analysis used in this study is an analysis of income. The analysis showed that the amount of income received by farmers is Rp. 22.100,914,06 / PS with an average effort of 1.60 ha. Reception is average Rp. 30.550.000,00 and the total average cost of Rp. 8.730.335,93/MT.Keywords: Income, Revenue, Production Input, Paddy Rice